Use of radio telemetry to determine presence of cattle stress indicators before slaughter - Paz Penagos, Hernán (Universidad Nacional de Colombia, 2019)
This study was conducted in order to determine the presence of stress in cattle prior to slaughter in situations such as loading, trans-porting, unloading, water and food deprivation during mobilization and waiting in the corral in overcrowded and inclement condi-tions. Samples were five bovines with ages of 40 months on average, castrated males, from the San Martinero criolla breed, whichwere transported along 144 Km, by land, from the farm located in Acacias, department of Meta, to the ICTA slaughter plant in Bo-gotá. The stress indicators were identified by differences in body temperature, heart rate and respiration frequency (hereinafter-physiological constants), which were monitored for 20 minutes at the time: prior to loading the animals on the farm, and uponarri-val at the slaughterhouse (just after being transported). The bovine cardiac signal was captured and processed through a girth, and was transmitted via a radio telemetry system that was designed and built in the project. The results show data capture at a sample rate of four million samples per second and wireless communication in real time, which meant that no information was lost on thevariations of the bovine heart signal and reception of information from any point of the slaughter plant.

Este estudio se realizó para determinar la presencia de estrés en bovinos antes de su sacrificio en situaciones de carga, transporte, descarga, privación de agua y alimento durante la movilización y espera en el corral en condiciones de hacinamiento y a la intem-perie. Las muestras fueron cinco bovinos de 40 meses en promedio, machos castrados, de raza criolla San Martinero, que fuerontransportados a lo largo de 144 Km, por vía terrestre, desde la finca ubicada en Acacias, departamento del Meta, hasta la plantade sacrificio del Instituto de Ciencia y Tecnología de Alimentos ICTA en Bogotá. Los indicadores de estrés se identificaron mediante diferencias de valores de temperatura corporal, frecuencia cardiaca y frecuencia respiratoria (en adelante constantes fisiológicas), que fueron monitoreadas durante 20 minutos en tiempos: previo a la carga de los animales en finca, y a la llegada al matadero(justo después de ser transportados). La señal cardiaca del bovino fue capturada y procesada a través de una cincha, y transmitida mediante un sistema de radiotelemetría que fue diseñado y construido en el proyecto. Los resultados evidencian captura de infor-mación a una tasa de muestreo de cuatro millones de muestras por segundo y comunicación inalámbrica en tiempo real, lo que hizo que no se perdiera información de las variaciones de la señal cardiaca del bovino y recepción de información desde cualquier punto de la planta de sacrificio.
Uso de la radio telemetría para determinar presencia de indicadores de estrés de bovinos antes de su sacrificio
Keywords: Calor animal; Animal heat; Ritmo cardíaco; Heart beat; Cattle; Telemetry radio; Indicators of stress; Sacrifice; Bovinos; Radio telemetría; Indicadores de estrés; Sacrificio